Seven Challenges for Arabic Department Students in Memorizing Hadith - Wulandari Wulandari; Syaza El Millah; Torkis Lubis; Zainul Arifin (Journal of Arabic Literature, Teaching and Learning, 2025)
Memorizing hadith is an activity that cannot be separated from the routine of Islamic studies students in fulfilling the demands of the course. But in reality there are still students who have difficulty memorizing hadith. So it is necessary to conduct a study to find out these difficulties. This study aims to find out how the difficulties of students in memorizing hadith. This research uses qualitative methods with the type of case study. The research data were taken through direct interviews with eleven students at one of the Arabic language education institutions in Padang, Indonesia. All interview data were then analyzed thematically using the Miles and Huberman analysis technique. The findings of the study showed seven difficulties of students in memorizing hadith, the seven difficulties are i) not proficient in reading Arabic texts, ii) not knowing the translation of hadith, iii) not understanding the content of hadith, iv) not used to memorizing hadith, v) laziness often arises, vi) the matan of hadith is too long, vii) the mufradat in hadith is garibah. The findings in this study have proven that students experience difficulties in memorizing hadith. The results of this study can be used as a reference for further research in examining this discussion in other contexts.